Peran Promosi, Persepsi Harga dalam Meningkatkan Keputusan Pembelian Kcharis Tenun Jumputan Palembang - Suharja, Taufik Hidayat Ria; Artina, Nyimas (MDP Student Conference, 2025)
This research aims to determine the role of promotion, price perception on purchasing decisions at KC Haris Jaya Tenun Jumputan Tuan Kentang, Palembang City. The research employs a quantitative descriptive method, with purposive sampling and multiple regression analysis using SPSS version 26. Respondents were buyers from KC Haris Jaya with a sample of 100 respondents. The results of the research are that promotions, price perceptions have a positive and significant influence on purchasing decisions at KC Haris Jaya Tenun Jumputan Tuan Kentang, Palembang City, partially or simultaneously.